2004
DOI: 10.1111/j.1440-1614.2004.01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Seclusion use with children and adolescents: an Australian experience

Abstract: There are patient factors that predict increased risk of seclusion; these factors and their interrelationships require further elucidation. Further research is also needed on the outcomes, both positive and negative, of seclusion use and of alternatives to seclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 27 publications
4
35
2
2
Order By: Relevance
“…Fryer et al (2004) found that children and adolescents with diagnoses of mental retardation, developmental disability and neurological impairment were likely to experience higher rates of seclusion, which replicates research evidence that increased rates of seclusion are seen in patients with poor communication and problem-solving skills. Rates of seclusion use varied from 19 to 60 percent and the main indication was for the management of aggression, which is largely in line with rates reported in other studies (Troutman et al, 1998).…”
Section: Physical Restraintsupporting
confidence: 71%
“…Fryer et al (2004) found that children and adolescents with diagnoses of mental retardation, developmental disability and neurological impairment were likely to experience higher rates of seclusion, which replicates research evidence that increased rates of seclusion are seen in patients with poor communication and problem-solving skills. Rates of seclusion use varied from 19 to 60 percent and the main indication was for the management of aggression, which is largely in line with rates reported in other studies (Troutman et al, 1998).…”
Section: Physical Restraintsupporting
confidence: 71%
“…After applying the inclusion criteria, 13 publications were excluded: 6 did not meet the time-frame [2,10,20,23,31,35]; 2 papers did not report original research [8,13] and 5 did not present prevalence data for seclusion or restraint use [8,19,28,26,33] Four of the 7 included studies had a pre-intervention/post-intervention design (n=1,302) [6,17,18,21], two were descriptive studies (n=590) [9,15], and the last one was a cross-sectional survey (n=504) [32] (Table 1). …”
Section: Search Resultsmentioning
confidence: 99%
“…One study found that male and female inpatients who experienced physical abuse, as well as female inpatients who experienced abuse of any kind, were more likely to have been secluded or restrained at least once while living on a child/adolescent psychiatric ward (Fryer et al, 2004). Another study in a children's psychiatric unit found that those who had experienced physical and/or sexual abuse were more likely to have been placed in seclusion while residing in the unit (Millstein & Cotton, 1990).…”
mentioning
confidence: 97%